Effect of design parameters of magnetic separator on recovery of metal values from slag waste. (3rd May 2023) - Harichandan, Barun; Venugopal, R.
Slag generated during the metallurgical processing of iron and steelmaking is principally a mixture of metallic oxide along with silica and other compounds. Although slag is an end waste generated during iron and crude steel production, it comprises a significant amount of metal values. The prime objective of this study is to recover the valuable metals present in the slag waste to minimise the waste generation as well as the adverse impact of disposal on the environment. This study focused on the recovery of magnetic material from steel slag by a magnetic separator based on its mineralogical characteristics and chemical composition. A full factorial experiment was designed for this investigation, and the obtained results were analysed by a mathematical model to validate the effect of process parameters on metal recovery. The optimum conditions were identified, and a confirmation test was also performed at that condition. Recovery of magnetic metal values over 93% was obtained, and the linear regression analysis indicated that the predicted values are in good agreement with the experimental results.